2014
DOI: 10.1093/infdis/jiu089
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gardnerella vaginalis in the Pathogenesis of Bacterial Vaginosis: A Conceptual Model

Abstract: G. vaginalis is the pathogen responsible for the initiation of BV. Future research should focus on preventing its transmission and improved therapeutics for the biofilm infection that is caused by this pathogen and host anaerobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
168
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(185 citation statements)
references
References 49 publications
3
168
1
13
Order By: Relevance
“…These investigators also tested endometrial fluid and tissue for cytokines and defensins and showed that colonization of the upper FRT with low levels of vaginal species is not associated with increased levels of inflammatory markers. Furthermore, Schwebke and colleagues (15,16) hypothesize that G. vaginalis initiates the formation of biofilms composed of diverse anaerobic and microaerophilic bacteria. It is possible that G. vaginalis individually does not induce an overt proinflammatory response; however, it may require the complex polymicrobial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators also tested endometrial fluid and tissue for cytokines and defensins and showed that colonization of the upper FRT with low levels of vaginal species is not associated with increased levels of inflammatory markers. Furthermore, Schwebke and colleagues (15,16) hypothesize that G. vaginalis initiates the formation of biofilms composed of diverse anaerobic and microaerophilic bacteria. It is possible that G. vaginalis individually does not induce an overt proinflammatory response; however, it may require the complex polymicrobial community.…”
Section: Discussionmentioning
confidence: 99%
“…The role of G. vaginalis in BV is still controversial. Schwebke and colleagues hypothesize that G. vaginalis is sexually transmitted and initiates polymicrobial biofilm formation (15,16). Importantly, BV has a high recurrence rate and is difficult to treat (17).…”
mentioning
confidence: 99%
“…In fact, different hypothesis have been considered to find out the principal trigger of the BV; one of them is the racial and societal differences, in which African American women have a higher probability to contract BV than European women because of their different vaginal pH [7]. Another hypothesis for the BV pathogenesis sees the G. vaginalis as the key-stone pathogen, which through its metabolic pathways and ability to form a biofilm, lowers the reduction-oxidation potential in the vaginal microbiome and then causes a marked decrease in lactobacilli and an increase in BVassociated bacteria [8].…”
Section: Interpretative Criteria Of Vaginal Smearsmentioning
confidence: 99%
“…BV results from vaginal dysbiosis characterized by a shift in commensal saprophytic vaginal microflora dominated by lactobacilli, to a microflora dominated by facultative and strict anaerobes (Hillier, 1993). While still poorly understood and categorized due to probable multifactorial origins (Reid, 2018), BV is linked in most cases to the presence of Gardnerella vaginalis (Schwebke et al, 2014;Hay, 2017), which can produce a biofilm that is not degraded by antibiotic treatment and that protects the bacteria against antibiotherapy (Thellin et al, 2016). One consequence is that numerous patients suffer from recurrent infections (Bradshaw et al, 2006;Sobel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%